Управління якістю біохімічного очищення стічних вод - Yeremeev, I. S.; Dichko, A. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
The approach to the control of wastewater treatment process, which is based on the usage of fuzzy sets theory methods, is proposed. To implement the method of expert estimation of membership functions the control rules of choice of the method of increasing process effectiveness and also linguistic variables that characterize treatment process, are defined. Example of membership function formation and heuristics for wastewater biochemical treatment intensification procedures is given. Qualitative monitoring of wastewater biochemical treatment process is proposed to ensure by use of Bayesian theorem with the aim of definition and detailing of reality probability of accepted hypothesis of control process parameters distribution under uncertainty.